Scales and danger of floods in the North Caucasus - Viktor Vladimirovich Razumov; Mukhtar Yusubovich Bekkiev; Natalia Victorovna Razumova; Sergey Ivanovich Shagin (Наука. Инновации. Технологии)
Results of systematization and the analysis of various sources containing information on scales of distribution and danger of manifestation of floods in the North Caucasus are considered. It is shown that activization of these processes in the territory of the studied region happens generally at the expense of spring high waters and summer and spring floods. The characteristic of the occurred floods and consequences of their manifestation in the territory of territorial subjects of the Russian Federation within the studied region is given. Are analysed, the occurred for the last 25 years in the territory of the region, emergency situations caused by floods. It is shown that annually in the region there are about 2 emergencies caused by floods. The greatest number of hydrological emergencies occurs in the Karachay-Cherkess Republic (23,9 % of all emergencies in the region caused by floods), Kabardino-Balkar Republic (21,7 %) and the Republic of Dagestan (17,4 %). The smallest - in the Republic of Ingushetia and Stavropol Krai (on 6,5 %). Most often these emergency situations happen on the territory of the region in June (about 40 % of all emergencies of hydrological character) and May (26,0 %). For summer months 67,4 % of all emergencies in the region caused by loods are necessary.